Tourism Potential of MICE (Meetings, Incentives, Conferences, and Exhibitions) with SWOT Analysis in Asahan Regency in North Sumatra Province - Muhammad Halfi Indra Syahputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of this study is to investigate Asahan Regency's strengths, weaknesses, opportunities, and threats related to MICE tourism management. Using a SWOT (Strength, Weakness, Opportunities, Threats) analysis, the used method is descriptive qualitative. As a result of the research, it can be observed that Asahan Regency remains in S< W and O≥T, necessitating internal consolidation; nevertheless, the O≥T has development potential. By addressing deficiencies and bolstering strengths in detail, the fundamental weaknesses are the absence of a tourism information center, the absence of branding or a brand name, the absence of business investors, the absence of promotions for adequate lodging, and the presence of a lot of road access that has not been optimized for cross-road or infrastructure that has not been fully exploited.